On the correlation of psychological characteristics within recreational marathon runners - Oschwald, Miles (2015)
Oschwald Miles, 2015. On the Correlation of Psychological Characteristics Within Recreational Marathon Runners. Master’s Thesis in Sport and Exercise Psychology. Department of Sport Science. University of Jyväskylä. University of Jyväskylä. 40 p.